2009
DOI: 10.1016/j.bbagen.2008.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Iron homeostasis and eye disease

Abstract: Summary Iron is necessary for life, but excess iron can be toxic to tissues. Iron is thought to damage tissues primarily by generating oxygen free radicals through the Fenton reaction. We present an overview of the evidence supporting iron's potential contribution to a broad range of eye disease using an anatomical approach. Firstly, iron can be visualized in the cornea as iron lines in the normal aging cornea as well as in diseases like keratoconus and pterygium. In the lens, we present the evidence for the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 129 publications
(158 reference statements)
2
84
1
4
Order By: Relevance
“…Iron is crucial for cell survival, and stable transferrin expression has been demonstrated to play a major role in iron homeostasis within the retina (43). Iron storage is regulated by ferritin and iron export by proteins such as ceruloplasmin, ferroportin, and hephaestin, and transferrin is involved in iron import into the cell (44).…”
Section: Discussionmentioning
confidence: 99%
“…Iron is crucial for cell survival, and stable transferrin expression has been demonstrated to play a major role in iron homeostasis within the retina (43). Iron storage is regulated by ferritin and iron export by proteins such as ceruloplasmin, ferroportin, and hephaestin, and transferrin is involved in iron import into the cell (44).…”
Section: Discussionmentioning
confidence: 99%
“…The latter has been correlated with DNA oxidation and down-regulation of p53 (40). Interestingly, it has been suggested that the presence of iron deposits along the corneal head of pterygium may indicate oxidative stress affecting local epithelial cells and resulting in disturbed iron homeostasis (35). The topical use of antioxidants as an adjuvant treatment option for pterygium would thus seem logical and should be investigated in future research projects.…”
Section: Concepts Of Inheritancementioning
confidence: 99%
“…The presence of Stocker's line along the head of pterygia lacking growth potential, as previously mentioned, may represent abnormal local iron metabolism along the advancing head of pterygium. Iron itself may be associated with increased free radical formation through biochemical (Fenton) reactions (35).…”
Section: Concepts Of Inheritancementioning
confidence: 99%
“…При некоторых заболеваниях глаз выявляют на-рушение минерального обмена в тканях, отводя особую роль Fe [22,23]. Отложение пигмента неред-ко происходит именно в роговице.…”
Section: Sem-edsunclassified